How Tokopedia Ads Exploits Call to Action Behaviour on Indonesia Marketplace Customers - Retno Purwani Sari; N R Dewi (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
The paper aims to discuss how Tokopedia, Indonesia’s largest marketplace, uses call to action (CTA) promotions to influence customer purchasing behaviour, whether the CTA creates a sense of urgency. The use of questionnaires enabled the collection of estimates of small and medium-sized enterprises’ (SMEs) readiness for Tokopedia’s CTA. Words, pictures, and narrative analysis with the Creswell mixed method determine how words, pictures, and narrative of five samples of CTA influence customers’ purchasing behaviour. Chris Fill (2013) on media and digital marketing and Alan Bashinsky (2016) ideas on CTA are included to further discuss the issue. The ranges of the success of Tokopedia’s CTA strategy were determined, resulting in the classification of strategies into the groups of fear, inclusion, anger, love, freedom, and curiosity according to emotional appeals in the CTA. Being tempted to buy specific items and ending up with a digital cart in a marketplace may indicate the success of the CTA strategy. Using CTA phrases, Tokopedia has successfully endorsed not only branded products from official stores but also high-quality products from SMEs. In summation, customer engagement improves when the majority of CTAs on Tokopedia use visual techniques and specific promotion times. Emotional engagement with each CTA can increase its effectiveness with customers. The study impacted upon the fact that CTA powers to lead and sell accelerate digital activities to improve the economy’s productivity.